The implementation of multiples intelligences theory on french teaching method for young learners age of 6-10 (level A1 of Institut Français d'Indonésie) - Anna Meifarolina; Miftahulkhairah Anwar; Hanip Pujiati (Franconesia, 2023)
The teaching method is one important aspect of the language skills of french language teaching. The method affects many things, one of which is the concentration level of children's learning in class. Therefore, of course, it is important to choose a teaching method that suits student needs. Unfortunately, at this time, language teachers tend to equate language teaching methods with language teaching methods for adults so that students who are at the vulnerable age are children (6 to 10 years). This teaching method for them is boring and results in a loss of concentration in their learning after 30 minutes of learning activities. Apparently, this is due to their different learning interests. This interest in learning is caused by a different type of intelligence called The Multiple Intelligences. This type of intelligence includes Linguistic Intelligence, Logical- Mathematical Intelligence, Visual Intelligence, Spatial Intelligence, Musical Intelligence, Intrapersonal Intelligence, Interpersonal Intelligence and Naturalist Intelligence. The method used in teaching foreign languages, especially in french language, should cover various types of student intelligence so that they can produce french teaching methods that can maximize children's language skills. Regarding children's French language skills, the ability to emphasize here is speaking ability because at their age speaking ability is the dominant ability students use in communicating because they have not been able to carry out correspondence activities, therefore language teaching is focused on teaching speaking skills.